Adhesive composition, and adhesive, adhesive sheet, and laminate made using the same
The adhesive composition, comprising an acrylic resin, liquid epoxy compound, mercapto-silane coupling agent, and epoxy curing agent, addresses the challenge of maintaining adhesive strength in humid and heat environments, achieving strong and durable adhesion in diverse applications.
Patent Information
- Application Number
- JP2021036380
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-08
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-03-08
AI Technical Summary
Existing pressure-sensitive adhesive compositions face challenges in maintaining adhesive strength when exposed to humid and heat environments, despite having good shear strength after curing.
A pressure-sensitive adhesive composition combining an acrylic resin with a specific glass transition temperature, a liquid epoxy compound, a silane coupling agent with mercapto groups, and an epoxy compound curing agent, which together provide moderate adhesive properties before curing, strong adhesive strength after curing, and high durability in wet and heat environments.
The adhesive composition achieves excellent adhesive strength both before and after exposure to humid and heat environments, making it suitable for various applications including building materials, in-vehicle parts, and electronic components.
Smart Images

Figure 0007655011000001 
Figure 0007655011000002 
Figure 0007655011000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a pressure-sensitive adhesive composition, more specifically to a pressure-sensitive adhesive that has adhesiveness at room temperature and that, after being applied to an adherend, cures upon heating to provide strong adhesion. The present invention also relates to a pressure-sensitive adhesive, a pressure-sensitive adhesive sheet, and a laminate that, after curing, exhibit little decrease in adhesive strength even when exposed to a humid and hot environment for a long period of time. [Background technology]
[0002] Liquid adhesives using epoxy compounds have traditionally been used to bond metals and plastics. Recently, thermosetting pressure-sensitive adhesive compositions using acrylic resins, epoxy resins, and epoxy curing agents have been proposed as pressure-sensitive adhesives that have the properties of both pressure-sensitive adhesives and adhesives, i.e., they are adhesive under normal conditions and cure by heating after being applied to an adherend to form a strong bond (see, for example, Patent Documents 1 and 2). Furthermore, pressure-sensitive adhesives using acrylic resins with silane coupling agents have been proposed with the aim of suppressing the decrease in adhesion in a humid and hot environment (see, for example, Patent Document 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Publication No. 2020-100806 [Patent Document 2] Japanese Patent Application Publication No. 2020-83998 [Patent Document 3] Japanese Patent Application Laid-Open No. 2012-171991 Summary of the Invention [Problem to be solved by the invention]
[0004] However, although the techniques disclosed in Patent Documents 1 and 2 above are excellent in shear strength after curing, they are poor in the ability to prevent a decrease in adhesive strength in a humid and hot environment (humid and heat resistance). Furthermore, even if the pressure-sensitive adhesives described in Patent Documents 1 and 2 were simply combined with the silane coupling agent of Patent Document 3, it was still not possible to suppress the change in adhesive strength before and after exposure to a humid and hot environment.
[0005] In view of the above, the present invention provides a pressure-sensitive adhesive composition that can provide a pressure-sensitive adhesive that has appropriate adhesiveness before curing, has excellent adhesive strength when thermally cured after bonding members together, and can maintain high adhesive strength even after being placed in a humid and hot environment. [Means for solving the problem]
[0006] However, the present inventors have conducted extensive research in light of these circumstances and have found that by using a specific amount of a liquid epoxy compound in an acrylic resin having a specific glass transition temperature (Tg), and further using a silane coupling agent having a mercapto group, it is possible to obtain a pressure-sensitive adhesive that has excellent adhesive performance even at room temperature before curing, exhibits strong adhesive strength after curing, and can maintain high adhesive strength even after exposure to a humid and hot environment.
[0007] That is, the gist of the present invention is as follows. <1> A pressure-sensitive adhesive composition comprising an acrylic resin (A), an epoxy compound (B) (excluding (A)) that is liquid at 25°C, a silane coupling agent (C), and a curing agent for an epoxy compound (D), The glass transition temperature of the acrylic resin (A) is −45 to 60° C., the content of the epoxy compound (B) is 5 to 100 parts by weight relative to 100 parts by weight of the acrylic resin (A); A pressure-sensitive adhesive composition, wherein the silane coupling agent (C) is a silane coupling agent (C1) having a mercapto group. <2> The acrylic resin (A) has a weight average molecular weight of 100,000 or more. <1> The adhesive composition described above. <3> The epoxy compound (B) is characterized in that it contains an epoxy compound having at least two epoxy groups in one molecule. <1> or <2> The adhesive composition described above. <4> The content of the silane coupling agent (C) is 0.01 to 3 parts by weight based on 100 parts by weight of the acrylic resin (A). <1> ~ <3> The adhesive composition according to any one of the preceding claims. <5> The curing agent (D) for epoxy compounds is a powder curing agent. <1> ~ <4> The adhesive composition according to any one of the preceding claims. <6> The composition further contains a crosslinking agent (E) for acrylic resins. <1> ~ <5> The adhesive composition according to any one of the preceding claims. <7> <1> ~ <6> 1. A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition according to any one of the preceding items. <8> It is characterized by being hardened by heating at 100 to 250°C. <7> The adhesive described above. <9> <7> or <8> 10. An adhesive sheet comprising an adhesive layer made of the adhesive described in . <10> <7> or <8> 10. A laminate comprising an adhesive layer made of the adhesive according to claim 1 and another member laminated thereon. [Effects of the Invention]
[0008] The pressure-sensitive adhesive composition of the present invention is capable of obtaining a pressure-sensitive adhesive that has tack and appropriate adhesive strength before curing, and has excellent adhesive strength after curing, and can further maintain high adhesive strength even after being placed in a moist and heat-resistant environment.
[0009] Therefore, the pressure-sensitive adhesive layer of the present invention can be suitably used for various applications, such as pressure-sensitive adhesive applications for building materials, in-vehicle parts, electronic parts, heat dissipation sheets, flexible printed circuit (FPC) manufacturing, semiconductor manufacturing processes, component sealing, aircraft parts, and sporting goods. DETAILED DESCRIPTION OF THE INVENTION
[0010] The present invention will be described in detail below. In the present invention, "(meth)acrylic" means acrylic or methacrylic, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylate" means acrylate or methacrylate, respectively. Moreover, the term "acrylic resin" refers to a resin obtained by polymerizing a polymerization component containing at least one type of (meth)acrylate monomer.
[0011] In the present invention, the term "adhesive" refers to an adhesive material that has tack at room temperature (23°C) before hardening, and hardens with an increased adhesive strength when triggered by heat or the like.
[0012] In the present invention, "curing" refers to curing of an epoxy compound by heating, and "crosslinking" (described later) refers to crosslinking of an acrylic resin, particularly crosslinking by reaction with a crosslinking agent.
[0013] The pressure-sensitive adhesive composition of the present invention contains an acrylic resin (A), an epoxy compound (B) that is liquid at 25°C, a mercapto silane coupling agent (C), and a curing agent for epoxy compounds (D). These components will be explained in order below.
[0014] <Acrylic resin (A)> The acrylic resin (A) in the present invention must have a glass transition temperature (Tg) of -45 to 60°C. If the Tg is too low below the above range, the adhesive strength after curing will not be sufficient, and if it is too high, the tackiness at room temperature will decrease. The acrylic resin (A) is a resin obtained by polymerizing a polymerization component containing at least one kind of (meth)acrylic monomer, and examples thereof include acrylic resins obtained by polymerizing a polymerization component containing a (meth)acrylic monomer as the main component and, in some cases, various other polymerizable monomers.
[0015] The phrase "mainly composed of" a (meth)acrylic monomer means that the (meth)acrylic monomer accounts for typically 40% by weight or more, preferably 50% by weight or more, and more preferably 60% by weight or more of the total polymerizable components. The upper limit is typically 100% by weight.
[0016] Examples of the (meth)acrylic monomer include (meth)acrylic acid or a derivative thereof, and (meth)acrylamide or a derivative thereof.
[0017] Examples of the derivatives of (meth)acrylic acid include alkyl group-containing (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, 2-methyl-2-nitropropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, n-pentyl (meth)acrylate, t-pentyl (meth)acrylate, 3-pentyl (meth)acrylate, 2,2-dimethylbutyl (meth)acrylate, n-hexyl (meth)acrylate, cetyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 4-methyl-2-propylpentyl (meth)acrylate, and n-octadecyl (meth)acrylate.
[0018] Other examples of the derivatives of (meth)acrylic acid include cycloalkyl (meth)acrylates such as cyclohexyl (meth)acrylate and cyclopentyl (meth)acrylate; aralkyl (meth)acrylates such as benzyl (meth)acrylate; biphenyloxy structure-containing (meth)acrylates such as biphenyloxyethyl (meth)acrylate; 2-isobornyl (meth)acrylate, 2-norbornylmethyl (meth)acrylate, 5-norbornen-2-yl-methyl (meth)acrylate, 3-methyl-2-norbornylmethyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxy Examples of the methacrylate include polycyclic (meth)acrylates such as ethyl (meth)acrylate and dicyclopentanyl (meth)acrylate; and alkoxy group- or phenoxy group-containing (meth)acrylates such as 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, methoxydiethylene glycol (meth)acrylate, ethoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethyl carbitol (meth)acrylate, phenoxyethyl (meth)acrylate, and alkylphenoxypolyethylene glycol (meth)acrylate.
[0019] Further, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate, hydroxyl group-containing (meth)acrylates such as [4-(hydroxymethyl)cyclohexyl]methyl acrylate, cyclohexanedimethanol mono(meth)acrylate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate, and epoxy group-containing (meth)acrylates such as glycidyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate glycidyl ether, are also included. Examples of the acrylate include halogen-containing (meth)acrylates such as 2,2,2-trifluoroethyl (meth)acrylate, 2,2,2-trifluoroethylethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropentyl (meth)acrylate, heptadecafluorodecyl (meth)acrylate, and 3-chloro-2-hydroxypropyl (meth)acrylate; alkylaminoalkyl (meth)acrylates such as dimethylaminoethyl (meth)acrylate; and oxetane group-containing (meth)acrylates such as 3-oxetanylmethyl (meth)acrylate, 3-methyloxetanylmethyl (meth)acrylate, 3-ethyloxetanylmethyl (meth)acrylate, 3-butyloxetanylmethyl (meth)acrylate, and 3-hexyloxetanylmethyl (meth)acrylate.
[0020] Examples of the (meth)acrylamide derivatives include N-alkyl group-containing (meth)acrylamide derivatives such as N-methyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, and N-hexyl(meth)acrylamide; N-hydroxyalkyl group-containing (meth)acrylamide derivatives such as N-methylol(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, and N-methylol-N-propane(meth)acrylamide; aminomethyl(meth)acrylamide; N-aminoalkyl group-containing (meth)acrylamide derivatives such as N-methoxymethyl(meth)acrylamide and N-ethoxymethyl(meth)acrylamide; N-mercaptoalkyl group-containing (meth)acrylamide derivatives such as mercaptomethyl(meth)acrylamide and mercaptoethyl(meth)acrylamide; and heterocycle-containing (meth)acrylamide derivatives such as N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, and N-acryloylpyrrolidine.
[0021] These (meth)acrylic monomers may be used alone or in combination of two or more. Among these (meth)acrylic monomers, (meth)acrylic acid alkyl esters are preferably used. The number of carbon atoms in the alkyl group in the (meth)acrylic acid alkyl ester is usually 1 to 20, preferably 1 to 12, and more preferably 1 to 8. The smaller the number of carbon atoms in the alkyl group, the better the compatibility with the epoxy compound (B) described below.
[0022] Among these (meth)acrylic monomers, the content of the monomer having an acryloyl group is preferably 25% by weight or more, more preferably 35% by weight or more, based on the total polymerization components of the acrylic resin (A). The upper limit of the content of the monomer having an acryloyl group based on the total polymerization components of the acrylic resin (A) is 100% by weight. By increasing the content ratio of the monomer having an acryloyl group, excellent transferability after the formation of the pressure-sensitive adhesive layer is achieved without impairing the adhesiveness before curing, and handling properties are improved.
[0023] As such a monomer having an acryloyl group, acrylic acid or a derivative thereof, acrylamide or a derivative thereof, or the like can be selected from the various (meth)acrylic monomers mentioned above and used.
[0024] When an acrylic acid derivative is used as the monomer having an acryloyl group, for example, an acrylic acid derivative having a glass transition temperature of 0° C. or higher when a homopolymer is prepared is preferred because it has a high glass transition temperature and the molecular weight of the acrylic resin (A) can be easily increased. In particular, methyl acrylate is suitable in terms of polymerizability.
[0025] When an acrylamide derivative is used as the acryloyl group-containing monomer, dialkylacrylamide or N-acryloylmorpholine is preferred because of its high glass transition temperature and excellent compatibility with the epoxy compound (B). In particular, it is preferred to use an acrylamide derivative having a glass transition temperature of 0°C or higher when preparing a homopolymer, since this allows the glass transition temperature of the resulting acrylic resin (A) to be maintained high and improves adhesion to the adherend.
[0026] The polymerization components constituting the acrylic resin (A) may contain polymerizable monomers other than (meth)acrylic monomers (hereinafter referred to as "other polymerizable monomers"). Examples of the other polymerizable monomers include unsaturated carboxylic acids such as crotonic acid, maleic acid, maleic anhydride, fumaric acid, citraconic acid, glutaconic acid, itaconic acid, acrylamido-N-glycolic acid, and cinnamic acid; carboxylic acid vinyl ester monomers such as vinyl acetate, vinyl propionate, vinyl stearate, and vinyl benzoate; aromatic ring-containing monomers such as styrene and α-methylstyrene; acrylonitrile, methacrylonitrile, vinyl chloride, vinylidene chloride, alkyl vinyl ethers, vinyl toluene, vinylpyridine, vinylpyrrolidone, itaconic acid dialkyl esters, fumaric acid dialkyl esters, allyl alcohol, acrylic chloride, methyl vinyl ketone, allyl trimethylammonium chloride, and dimethylallyl vinyl ketone. These may be used alone or in combination of two or more.
[0027] The polymerization components constituting the acrylic resin (A) preferably contain a functional group-containing monomer. The functional group-containing monomer preferably contains at least one functional group-containing monomer selected from hydroxyl group-containing monomers and carboxyl group-containing monomers. Among these, considering the reactivity with the acrylic resin crosslinking agent (E) described below, at least one functional group-containing monomer selected from hydroxyl group-containing monomers and carboxyl group-containing monomers containing a (meth)acryloyl group is preferred. Examples of the hydroxyl group-containing monomer containing a (meth)acryloyl group include hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 4-hydroxybutyl acrylate. Among these, 2-hydroxyethyl (meth)acrylate is particularly preferred. The carboxyl group-containing monomer containing a (meth)acryloyl group is preferably (meth)acrylic acid.
[0028] The content of such functional group-containing monomer is preferably 0.1 to 30% by weight, more preferably 1 to 25% by weight, and even more preferably 3 to 20% by weight, based on the total polymer components constituting the acrylic resin (A). If the content is too high, the cohesive force when the adhesive layer is formed tends to decrease, and tackiness and reworkability tend to decrease. On the other hand, if the content is too high, the storage stability of the adhesive layer tends to decrease and the pot life tends to be shortened.
[0029] The carboxyl group content is preferably 0 to 3 wt%, more preferably 0.01 to 2 wt%, and even more preferably 0.05 to 1 wt%. If the content is too high, the storage stability of the adhesive tends to decrease, whereas if the content is too low, the adhesive strength after curing tends to decrease.
[0030] The polymerization method for the acrylic resin (A) can be a conventionally known method such as solution radical polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. For example, a method in which appropriately selected polymerization components and a polymerization initiator are mixed or dropped into an organic solvent and polymerized under predetermined polymerization conditions can be used. Among these, solution radical polymerization and bulk polymerization are preferred, and solution radical polymerization is particularly preferred because it allows the stable production of an acrylic resin.
[0031] Examples of organic solvents used in the polymerization reaction include aromatic hydrocarbons such as toluene and xylene, aliphatic hydrocarbons such as hexane, esters such as ethyl acetate and butyl acetate, aliphatic alcohols such as n-propyl alcohol and isopropyl alcohol, and ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone. These organic solvents may be used alone or in combination of two or more.
[0032] Among these organic solvents, in terms of ease of polymerization reaction, chain transfer effect, ease of drying when the pressure-sensitive adhesive composition is applied, and safety, esters such as ethyl acetate and butyl acetate; and ketones such as acetone, methyl ethyl ketone and methyl isobutyl ketone are preferred.
[0033] Examples of polymerization initiators used in such solution radical polymerization include azo initiators such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, 4,4'-azobis(4-cyanovaleric acid), and 2,2'-azobis(methylpropionic acid), which are common radical polymerization initiators; and organic peroxides such as benzoyl peroxide, lauroyl peroxide, di-t-butyl peroxide, and cumene hydroperoxide; and these can be appropriately selected and used depending on the monomer to be used. These polymerization initiators may be used alone or in combination of two or more.
[0034] In this way, the acrylic resin (A) used in the present invention is obtained.
[0035] The weight-average molecular weight (Mw) of the acrylic resin (A) is preferably 100,000 or more, more preferably 100,000 to 1,500,000, more preferably 150,000 to 1,000,000, and particularly preferably 200,000 to 800,000. If the weight-average molecular weight is too small, the toughness and cohesive strength of the resulting pressure-sensitive adhesive layer tend to decrease, and the adhesive performance and reworkability before curing tend to decrease. On the other hand, if the weight-average molecular weight is too large, the viscosity tends to become too high, resulting in increased scaling during polymerization and reduced compatibility with the epoxy compound (B) and reduced handleability.
[0036] The dispersity of the acrylic resin (A) [weight average molecular weight (Mw) / number average molecular weight (Mn)] is preferably 10 or less, more preferably 7 or less. If the dispersity is too high, the cohesive strength tends to decrease. The lower limit of the dispersity is usually 1.
[0037] The weight-average molecular weight of the acrylic resin (A) is the weight-average molecular weight converted into the molecular weight of standard polystyrene. The weight-average molecular weight was measured using a high-performance liquid chromatograph (manufactured by Japan Waters, "Waters 2695 (main unit)" and "Waters 2414 (detector)") with a column: Shodex GPC KF-806L (exclusion limit molecular weight: 2 × 10 7 Separation range: 100 to 2 × 107 The measurement can be performed using three tubes connected in series (theoretical plate number: 10,000 plates / tube, filler material: styrene-divinylbenzene copolymer, filler particle size: 10 μm), and the number average molecular weight can be measured in a similar manner. The dispersity can be determined from the measured values of the weight average molecular weight and number average molecular weight.
[0038] The glass transition temperature (Tg) of the acrylic resin (A) must be −45 to 60° C., more preferably −35 to 45° C., even more preferably −20 to 35° C., and particularly preferably −10 to 30° C. If the glass transition temperature is too low, the adhesive strength after curing tends to decrease, and if it is too high, the tack before curing tends to decrease.
[0039] The glass transition temperature is calculated by the following Fox formula.
number
[0040] That is, it is a value calculated by applying the glass transition temperature and weight fraction of each of the monomers constituting the acrylic resin when they are made into a homopolymer to the Fox formula. The glass transition temperature of a homopolymer of the monomers constituting the acrylic resin is usually measured by a differential scanning calorimeter (DSC), and can be measured by a method in accordance with JIS K7121-1987 or JIS K 6240.
[0041] The refractive index of the acrylic resin (A) is usually 1.440 to 1.600. It is preferable to make the difference in refractive index between the acrylic resin (A) and the member to be laminated small, since this reduces optical loss at the interface between the members.
[0042] The refractive index is a value measured by measuring the acrylic resin (A) in a thin film form using a refractive index measuring device (Abbe Refractometer 1T manufactured by Atago Co., Ltd.) at 23° C. using NaD rays.
[0043] <Epoxy compound (B) that is liquid at 25°C> The epoxy compound (B) used in the present invention is a compound having one or more epoxy groups in the molecule, excluding the acrylic resin (A). The epoxy compound (B) used in the present invention must be liquid at 25°C. In the present invention, "liquid" refers to a state in which the composition has fluidity, and preferably has a viscosity of 20,000 mPa·s / 25°C or less, more preferably 15,000 mPa·s / 25°C or less, even more preferably 13,000 mPa·s / 25°C or less, and particularly preferably 10,000 mPa·s / 25°C or less. The lower limit is usually 0.1 mPa·s / 25°C.
[0044] The epoxy compound (B) has one or more epoxy groups in one molecule, and preferably has two or more epoxy groups, more preferably from 2 to 6. If the number of epoxy groups is too large, the moist heat resistance tends to decrease.
[0045] Examples of monofunctional epoxy compounds having one epoxy group in the molecule include alkyl glycidyl ethers, alkoxy glycidyl ethers, phenol glycidyl ethers, EO (ethylene oxide)-modified phenol glycidyl ethers, and allyl glycidyl ethers.
[0046] Examples of bifunctional epoxy compounds having two epoxy groups in the molecule include neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, diglycidyl terephthalate, diglycidyl-o-phthalate, diglycidyl resorcinol ether, bisphenol A diglycidyl compounds and hydrogenated products thereof, bisphenol F diglycidyl compounds and hydrogenated products thereof, biphenyl diglycidyl compounds and derivatives thereof, and the like.
[0047] Examples of polyfunctional epoxy compounds having three or more epoxy groups in the molecule include trifunctional epoxy compounds such as glycerol triglycidyl ether, trimethylolpropane triglycidyl ether, triglycidyl isocyanurate and derivatives thereof, and pentaerythritol triglycidyl ether; tetrafunctional epoxy compounds such as pentaerythritol tetraglycidyl ether, diglycerol tetraglycidyl ether, and ditrimethylolpropane tetraglycidyl ether; pentafunctional epoxy compounds such as polyglycerol pentaglycidyl ether, pentaerythritol pentaglycidyl ether, and dipentaerythritol pentaglycidyl ether; hexafunctional epoxy compounds such as sorbitol hexaglycidyl ether and dipentaerythritol hexaglycidyl ether; polyglycidyl ethers, phenol novolac epoxy compounds, and cresol novolac epoxy compounds.
[0048] Furthermore, examples of compounds with a large epoxy equivalent weight, such as oligomer-type epoxy compounds and polymer-type epoxy compounds, include the following products. DIC: EXA-4850-150, EXA-4850-1000, TSR-960, Mitsubishi Chemical Corporation: jER YX-7700, jER YX-7400, jER828, jER871, jER890, jER YX8034, jER YX7105, ADEKA Corporation: EP-4100TX, EP-5100-75X, EP-4000, EP-7001, EPU-6, EPR-2000, ED-502, etc.
[0049] The epoxy equivalent of the epoxy compound (B) is preferably 150 to 5000 g / mol, more preferably 200 to 3000 g / mol, particularly preferably 250 to 1500 g / mol, and even more preferably 300 to 1000 g / mol. If the epoxy equivalent is within the above range, the adhesive strength after curing and the adhesive strength after a moist heat test tend to be well balanced.
[0050] In the present invention, the weight average molecular weight of the epoxy compound (B) is preferably 300 to 5000, more preferably 350 to 4000, and particularly preferably 400 to 2000. If the molecular weight is too small, the compound tends to volatilize during heat curing, easily generating bubbles and reducing reworkability, whereas if the molecular weight is too large, the viscosity tends to increase, and the tackiness of the resulting pressure-sensitive adhesive layer tends to decrease.
[0051] In the present invention, the content of the epoxy compound (B) must be 5 to 100 parts by weight relative to 100 parts by weight of the acrylic resin (A), more preferably 7.5 to 80 parts by weight, particularly preferably 10 to 60 parts by weight, and even more preferably 10 to 50 parts by weight. If the content of the epoxy compound (B) relative to the acrylic resin (A) is too low, the tack and adhesive strength of the pressure-sensitive adhesive layer before curing tend to decrease, while if it is too high, the storage stability of the pressure-sensitive adhesive layer tends to decrease. Furthermore, if the content is too high or too low, the adhesiveness tends to decrease when the pressure-sensitive adhesive layer is exposed to a humid and hot environment for a long period of time after curing.
[0052] Examples of such epoxy compounds (B) include monofunctional epoxy compounds having one epoxy group in the molecule and polyfunctional epoxy compounds having two or more epoxy groups. These compounds may be used alone or in combination of two or more.
[0053] <Silane coupling agent having a mercapto group (C)> The silane coupling agent (C) used in the present invention is a general term for silane compounds having an alkoxysilyl group and other functional groups. The silane coupling agent (C) in the present invention must have a mercapto group.
[0054] The alkoxysilyl group content in the silane coupling agent (C) is preferably 5 to 70% by weight, more preferably 10 to 60% by weight, and particularly preferably 15 to 50% by weight. The mercapto equivalent of the silane coupling agent (C) is preferably 150 to 3000 g / mol, more preferably 200 to 1500 g / mol, and particularly preferably 300 to 1000 g / mol.
[0055] Such a silane coupling agent (C) may be a monomer type or an oligomer type in which a part of the silane coupling agent is hydrolyzed and condensed. Among these, an oligomer type or a silane coupling agent having a molecular weight of 500 or more is preferred in terms of low volatilization during drying or heat curing, less generation of bubbles in the pressure-sensitive adhesive layer, and good resistance to moist heat.
[0056] Examples of commercially available silane coupling agents (C) for use in the present invention include the following products. Examples of monomer types include 3-mercaptopropylmethyldimethoxysilane "KBM-802" and 3-mercaptopropyltrimethoxysilane "KBM-803" manufactured by Shin-Etsu Chemical Co., Ltd. Examples of oligomer types include "X-41-1810," "X-41-1805," "X-41-1818," and "X-12-1154," manufactured by Shin-Etsu Chemical Co., Ltd. Other examples include "CoatOSil T-Cure" and "e-free 189 Silane" manufactured by Momentive.
[0057] The content of the silane coupling agent (C) used in the present invention is preferably 0.01 to 5 parts by weight, particularly preferably 0.01 to 3 parts by weight, further preferably 0.05 to 2 parts by weight, and particularly preferably 0.1 to 1.5 parts by weight, relative to 100 parts by weight of the acrylic resin (A). If the content is too low, the moist heat resistance tends to decrease, while if the content is too high, the adhesive strength immediately after curing tends to decrease.
[0058] <Curing agent for epoxy compounds (D)> The curing agent (D) for epoxy compounds used in the present invention is used as a curing agent for the epoxy compound (B) and is a compound having a functional group capable of reacting with an epoxy group. Examples of such epoxy compound curing agents (D) include amines, polyamides, imidazoles, polymercaptan curing agents, acid anhydrides, etc. These may be used alone or in combination of two or more. Among the above-mentioned epoxy compound curing agents (D), amine curing agents are preferred, particularly in terms of excellent storage stability and curing properties when made into a pressure-sensitive adhesive, and dicyandiamide and organic acid hydrazides are more preferred. Among organic acid hydrazides, adipic acid dihydrazide and sebacic acid dihydrazide are particularly preferred, particularly in terms of excellent curing speed.
[0059] The epoxy compound curing agent (D) may be a liquid or a solid, and is preferably a solid in terms of storage stability when formed into an adhesive and the pot life of the adhesive composition. Furthermore, a powder is preferred in terms of the coating film becoming smooth, increasing the adhesive area with the member upon curing, and increasing the adhesive strength after curing. Furthermore, it is preferred that such a powder be contained in a dispersed state in the adhesive. When a powder is used as the epoxy compound curing agent (D), the particle size of the powder is preferably set to be 1.2 times or less, more preferably 1 time or less, the thickness of the adhesive layer when formed.
[0060] The content of the curing agent for epoxy compounds (D) is preferably 1 to 100 parts by weight, more preferably 3 to 80 parts by weight, and particularly preferably 5 to 50 parts by weight, relative to 100 parts by weight of the epoxy compound (B). Alternatively, the amount (mol) of functional groups in the curing agent for epoxy compounds (D) is preferably 0.5 to 2 times, more preferably 0.6 to 1.5 times, and even more preferably 0.8 to 1.2 times the total amount (mol) of epoxy groups in the epoxy compound (B). If the content ratio of the epoxy compound curing agent (D) relative to the epoxy compound (B) is too low below the above range, the curing rate tends to be slow or the curing temperature tends to be high, whereas if the content ratio is too high, the strength of the coating film after curing tends to be reduced or the storage stability when made into a pressure-sensitive adhesive tends to be reduced.
[0061] <Crosslinking agent for acrylic resins (E)> The pressure-sensitive adhesive composition of the present invention contains the above-mentioned acrylic resin (A), epoxy compound (B), silane coupling agent (C), and curing agent for epoxy compound (D). It is preferable that the pressure-sensitive adhesive composition further contains a crosslinking agent for acrylic resin (E) (hereinafter, sometimes abbreviated as "crosslinking agent (E)") that crosslinks the acrylic resin (A). The inclusion of the crosslinking agent (E) makes it possible to crosslink the pressure-sensitive adhesive composition, which is advantageous in terms of increasing the cohesive strength of the pressure-sensitive adhesive and improving reworkability. Note that although the acrylic resin (A) is also crosslinked by the epoxy compound (B), the crosslinking agent (E) in the present invention does not include the epoxy compound (B) in that it crosslinks the acrylic resin (A) before thermal curing.
[0062] As the crosslinking agent (E) for acrylic resins, known crosslinking agents can be used, such as isocyanate-based crosslinking agents, aziridine-based crosslinking agents, melamine-based crosslinking agents, aldehyde-based crosslinking agents, and metal chelate-based crosslinking agents, and among these, isocyanate-based crosslinking agents are preferred. These crosslinking agents (E) may be used alone or in combination of two or more.
[0063] Examples of the isocyanate crosslinking agent include tolylene diisocyanate compounds such as 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate; xylylene diisocyanate compounds such as 1,3-xylylene diisocyanate, 1,4-xylylene diisocyanate and tetramethylxylylene diisocyanate; aromatic isocyanate compounds such as 1,5-naphthalene diisocyanate and triphenylmethane triisocyanate; hexamethylene diisocyanate, pentamethylene diisocyanate, isophorone diisocyanate, and adducts of these isocyanate compounds with polyol compounds such as trimethylolpropane; and biuret and isocyanurate forms of these polyisocyanate compounds.
[0064] Examples of the aziridine crosslinking agent include tetramethylolmethane-tri-β-aziridinylpropionate, trimethylolpropane-tri-β-aziridinylpropionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), and N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide).
[0065] Examples of the melamine-based crosslinking agent include hexamethoxymethylmelamine, hexaethoxymethylmelamine, hexapropoxymethylmelamine, hexabutoxymethylmelamine, hexapentyloxymethylmelamine, hexahexyloxymethylmelamine, and melamine resins.
[0066] Examples of the aldehyde crosslinking agent include glyoxal, malondialdehyde, succindialdehyde, maleic dialdehyde, glutaric dialdehyde, formaldehyde, acetaldehyde, and benzaldehyde.
[0067] Examples of the metal chelate crosslinking agent include acetylacetone and acetoacetyl ester coordination compounds of polyvalent metals such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, and zirconium.
[0068] The content of the crosslinking agent (E) used in the present invention is preferably 0 to 20 parts by weight, more preferably 0.1 to 15 parts by weight, particularly preferably 0.5 to 10 parts by weight, and even more preferably 1 to 5 parts by weight, relative to 100 parts by weight of the acrylic resin (A). If the content of such crosslinking agent (E) is too high, the tackiness of the pressure-sensitive adhesive layer when formed tends to decrease, whereas if the content is too low, the pressure-sensitive adhesive layer tends to be easily deteriorated due to thermal decomposition when exposed to high temperatures.
[0069] <Optional ingredients> In the present invention, in addition to the above components, various additives may also be contained as optional components, such as conductive agents such as carbon or metal; inorganic fillers such as metal particles or glass particles; tackifiers such as urethane resins, rosin, rosin esters, hydrogenated rosin esters, phenolic resins, aliphatic petroleum resins, alicyclic petroleum resins, and styrene-based resins; fillers; antioxidants; ultraviolet absorbers; crosslinking accelerators such as ionic compounds, peroxides, and urethane catalysts; and crosslinking retarders such as acetylacetone. These may be used alone or in combination of two or more.
[0070]
[0113] In addition to the optional components, the pressure-sensitive adhesive composition of the present invention may contain impurities and the like contained in raw materials for producing the components of the pressure-sensitive adhesive composition, to the extent that the effects of the present invention are not impaired.
[0071] <Adhesive composition> The pressure-sensitive adhesive composition of the present invention can be obtained by mixing the above-mentioned acrylic resin (A), epoxy compound (B), silane coupling agent (C), curing agent for epoxy compound (D), and, if necessary, crosslinking agent (E) and other components.
[0072] The method for mixing these components is not particularly limited, and various methods can be used, such as a method in which the components are mixed together at once, or a method in which any component is mixed and then the remaining components are mixed together or sequentially.
[0073] [Adhesive, adhesive sheet, and laminate] When the adhesive composition of the present invention contains a solvent, it can be dried to form an adhesive. Furthermore, by laminating an adhesive layer containing this adhesive on a substrate such as a plastic film, an adhesive sheet having a laminate structure of substrate / adhesive layer can be obtained. Furthermore, by laminating this adhesive layer on an adherend, a laminate having a laminate structure of adherend / adhesive layer can be obtained. Hereinafter, the substrate and the adherend will also be collectively referred to as "members."
[0074] The adhesive sheet includes, in addition to an adhesive sheet in which an adhesive layer is laminated on a substrate, a substrate-less double-sided adhesive sheet in which separators (release sheets) are laminated on both sides of the adhesive layer, and the double-sided adhesive sheet is preferred from the viewpoint of ease of handling.
[0075] The adhesive sheet can be produced, for example, by coating the adhesive composition on a substrate and drying it. When a crosslinking agent (E) is used, examples of the method include laminating a separator to the adhesive layer after drying, and performing an aging treatment by at least one of aging at room temperature (without heating) and aging at a temperature high enough to prevent the epoxy compound (B) from curing. A substrate-less double-sided adhesive sheet can also be produced by coating the adhesive composition on a separator and drying it, and then laminating another separator having a different peel strength to the separator, and performing an aging treatment.
[0076] The aging treatment is a treatment carried out when a crosslinking agent (E) is used, in order to chemically crosslink the acrylic resin (A) and the crosslinking agent (E) and thereby cause the pressure-sensitive adhesive to exhibit an appropriate cohesive strength. The aging conditions are, for example, a temperature that is usually from room temperature (20±10°C) to 40°C and a time that is usually from 1 to 30 days, and specific conditions include, for example, conditions at 23°C for 1 to 20 days and at 40°C for 1 to 7 days. When the crosslinking agent (E) is not used, the aging treatment is not necessarily required.
[0077] When applying the above adhesive composition, it is preferable to dilute the adhesive composition with a solvent before application, and the solid content concentration in the adhesive composition is preferably 5 to 65% by weight, more preferably 20 to 55% by weight. The solvent is not particularly limited as long as it dissolves or disperses the pressure-sensitive adhesive composition. For example, ester-based solvents such as methyl acetate, ethyl acetate, methyl acetoacetate, and ethyl acetoacetate; ketone-based solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; aromatic solvents such as toluene and xylene; and alcohol-based solvents such as methanol, ethanol, and propyl alcohol. Among these, ethyl acetate is preferably used in terms of solubility, drying properties, cost, and the like.
[0078] The viscosity of the diluted pressure-sensitive adhesive composition is preferably 500 to 30,000 mPa·s / 25° C., more preferably 1,000 to 10,000 mPa·s / 25° C. If the viscosity is too low, when a component with a high specific gravity is used, the component tends to settle, and the concentration of the component in the pressure-sensitive adhesive composition tends to become non-uniform.
[0079] Examples of the method for applying the pressure-sensitive adhesive composition include roll coating, die coating, gravure coating, comma coating, and screen printing.
[0080] The thickness of the adhesive layer in the adhesive sheet is preferably 5 to 250 μm, more preferably 25 to 200 μm, and even more preferably 50 to 175 μm. If the adhesive layer is too thin, the thickness precision and adhesive strength tend to decrease, whereas if the adhesive layer is too thick, when the adhesive sheet is rolled, the adhesive layer tends to protrude from the edges and contaminate the roll.
[0081] The gel fraction of the adhesive layer is preferably 0 to 99% by weight, more preferably 20 to 95% by weight, and even more preferably 30 to 80% by weight, from the viewpoints of adhesion to a member, reworkability, and adhesiveness before curing. If the gel fraction of the adhesive layer is too high, sufficient adhesion between the adhesive layer and the interface of the member may not be obtained when the adhesive sheet is bonded to a member, and the adhesive strength after curing tends to decrease. The lower limit of the gel fraction is usually 0% by weight.
[0082] The gel fraction is an index of the degree of crosslinking (degree of curing) and is calculated, for example, by the following method. First, an adhesive is picked from an adhesive sheet having an adhesive layer laminated on the surface of a substrate, and the adhesive is wrapped in a 200-mesh SUS wire mesh and immersed in ethyl acetate adjusted to 23°C for 24 hours. The weights of the adhesive are measured before and after immersion in ethyl acetate, and the difference between the two weights is taken as the weight of the insoluble adhesive remaining in the wire mesh. The weight percentage of the insoluble adhesive remaining in the wire mesh relative to the weight of the adhesive before immersion in ethyl acetate is taken as the gel fraction.
[0083] In the present invention, the adhesive has the function of being cured by heating at a predetermined temperature, and therefore the adhesive strength of the adhesive layer in the adhesive sheet increases, and the adhesive sheet is fixed to the adherend. The heating temperature when curing the pressure-sensitive adhesive is preferably 100 to 250°C, more preferably 120 to 200°C, and even more preferably 130 to 185°C. If the temperature is too low, the curing time becomes long and workability tends to decrease, while if the temperature is too high, the epoxy compound (B) tends to volatilize or ignite. The heating time is preferably 5 to 240 minutes, more preferably 30 to 180 minutes, and even more preferably 45 to 120 minutes. If the time is too short, curing tends to be insufficient and the adhesive strength tends to decrease, while if the time is too long, workability tends to decrease and the members to be bonded tend to deteriorate due to heat.
[0084] The adhesive sheet, in which an adhesive layer is laminated on the surface of a separator, allows the adhesive layer to be easily transferred by simply peeling off the separator and adhering the adhesive layer to the surface of a target adherend, resulting in very good work efficiency.
[0085]
[0042] Furthermore, in a laminate obtained by laminating another member via the pressure-sensitive adhesive layer, i.e., a laminate having a laminate structure of adherend / pressure-sensitive adhesive layer / other member, the pressure-sensitive adhesive layer has high adhesiveness before curing and exhibits high adhesive strength after curing, so that the other member is unlikely to easily slip off or peel from the adherend. Therefore, by using the pressure-sensitive adhesive of the present invention, a laminate having high adhesive reliability and excellent quality in appearance can be obtained.
[0086] The pressure-sensitive adhesive composition of the present invention can be attached to a member from a separator at room temperature (transferability) before curing, and has excellent coating film appearance and reworkability, and can form a pressure-sensitive adhesive that has excellent adhesion to an adherend after curing and also has excellent moist heat resistance.
[0063] Therefore, the pressure-sensitive adhesive composition of the present invention can be suitably used in various pressure-sensitive adhesive applications, such as for building materials, in-vehicle parts, electronic parts, semiconductor manufacturing processes, component sealing, aircraft parts, and sporting goods.
[0087] The present invention is particularly useful in applications involving flexible printed circuit boards (FPCs), such as bonding an FPC to a reinforcing plate. In applications involving bonding an FPC to a reinforcing plate, the adhesive can be attached to the adherend at room temperature without the need for heat lamination (thermal lamination), and the adhesive has good reworkability and excellent adhesive reliability after heat curing, making it extremely useful. [Example]
[0088] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight. In the following examples, the weight average molecular weight, dispersity, glass transition temperature and other physical properties of the acrylic resins were measured according to the methods described above. First, prior to the examples, the following components were prepared.
[0089] <Acrylic resin (A)> The following materials were prepared as raw materials for the acrylic resin (A): The polymerization components of the acrylic resin (A) and the physical properties of the acrylic resin are shown in Table 1 below.
[0090] [Preparation of acrylic resin (A-1)] A four-necked round-bottom flask equipped with a reflux condenser, a stirrer, a nitrogen gas inlet, and a thermometer was charged with 80 parts of ethyl acetate, 6 parts of methyl ethyl ketone, and 0.036 parts of azobisisobutyronitrile (AIBN) as a polymerization initiator. After heating, the mixture was heated to a boiling point. A mixture of 40 parts of methyl acrylate (MA), 10 parts of methyl methacrylate (MMA), 44.9 parts of n-butyl methacrylate (BMA), 5 parts of 2-hydroxyethyl acrylate (2HEA), 0.1 parts of acrylic acid (AAc), 4 parts of ethyl acetate, and 0.036 parts of AIBN was added dropwise over a period of 2 hours while maintaining the boiling state. After this, 0.05 parts of AIBN were added twice while the reaction was continued. After the reaction was continued for 7 hours, the mixture was diluted with ethyl acetate to obtain an acrylic resin (A-1) solution (solids concentration 42.2%, viscosity 5200 mPa·s / 25°C). The weight average molecular weight (Mw) of the obtained acrylic resin (A-1) was 246,000, the dispersity (Mw / Mn) was 2.4, and the glass transition temperature (Tg) was 19.7°C.
[0091] [Preparation of acrylic resin (A-2)] A four-neck round-bottom flask equipped with a reflux condenser, a stirrer, a nitrogen gas inlet, and a thermometer was charged with 88.8 parts of ethyl acetate, 1.3 parts of methyl ethyl ketone, and 0.025 parts of azobisisobutyronitrile (AIBN) as a polymerization initiator, and heated until the internal temperature reached the boiling point. Then, a mixed solution of 76.8 parts of n-butyl acrylate (BA), 20 parts of methyl methacrylate (MA), 3 parts of 2-hydroxyethyl acrylate (2HEA), 0.2 parts of acrylic acid (AAc), 5 parts of ethyl acetate, and 0.038 parts of the polymerization initiator (AIBN) was added dropwise over 2 hours while maintaining the boiling state. Then, while continuing the reaction, 0.038 parts of a polymerization initiator (AIBN) and 0.038 parts of azobisdimethylvaleronitrile (ADVN) were added in that order, and after reacting for 7 hours, the mixture was diluted with ethyl acetate to obtain an acrylic resin (A-2) solution (solids concentration 39.6%, viscosity 7000 mPa·s / 25°C). The weight average molecular weight (Mw) of the obtained acrylic resin (A-2) was 700,000, the polydispersity (Mw / Mn) was 4.7, and the glass transition temperature (Tg) was -44°C.
[0092] [Preparation of acrylic resin (A'-1)] A four-necked round-bottom flask equipped with a reflux condenser, a stirrer, a nitrogen gas inlet, and a thermometer was charged with 90 parts of ethyl acetate and 0.025 parts of azobisisobutyronitrile (AIBN) as a polymerization initiator. After heating, the mixture was heated to the boiling point. A mixture of 96.8 parts of n-butyl acrylate (BA), 3 parts of 2-hydroxyethyl acrylate (2HEA), 0.2 parts of acrylic acid (AAc), 5 parts of ethyl acetate, and 0.038 parts of the polymerization initiator (AIBN) was added dropwise over 2 hours while maintaining the boiling state. Then, while continuing the reaction, 0.038 parts of the polymerization initiator (AIBN) and 0.038 parts of azobisdimethylvaleronitrile (ADVN) were sequentially added. After 7 hours of reaction, the mixture was diluted with ethyl acetate to obtain an acrylic resin (A'-1) solution (solids concentration 39.2%, viscosity 2500 mPa·s / 25°C). The weight average molecular weight (Mw) of the obtained acrylic resin (A'-1) was 650,000, the dispersity (Mw / Mn) was 5.4, and the glass transition temperature (Tg) was -55°C.
[0093] <Epoxy compound (B)> The following epoxy compounds (B) were prepared. (B-1): jER YX7400 (manufactured by Mitsubishi Chemical Corporation, viscosity 200 mPa·s / 25°C, epoxy equivalent 440 g / mol, two epoxy groups per molecule) (B-2): jER 828 (manufactured by Mitsubishi Chemical Corporation, viscosity 13,500 mPa·s / 25°C, epoxy equivalent 189 g / mol, Mw 370, two epoxy groups per molecule)
[0094] <Silane coupling agent (C)> The following silane coupling agent (C) was prepared. (C-1): E-free J189 (a silane coupling agent having a mercapto group, manufactured by Momentive) (C-2): X-41-1810 (silane coupling agent having a mercapto group, manufactured by Shin-Etsu Chemical Co., Ltd.) (C'-1): KR-516 (a silane coupling agent having an epoxy group, manufactured by Shin-Etsu Chemical Co., Ltd.)
[0095] <Curing agent for epoxy compounds (D)> The following was prepared as a curing agent (D) for epoxy compounds. (D-1): Adipic acid dihydrazide (ADH-S, manufactured by Otsuka Chemical Co., Ltd., powder)
[0096] <Crosslinking agent for acrylic resin (E)> The following crosslinking agent (E) for acrylic resin was prepared. (E-1): Coronate L55E (an adduct of trimethylolpropane and tolylene diisocyanate, manufactured by Tosoh Corporation)
[0097] <Examples 1 to 4 and Comparative Examples 1 to 6> The above components were blended according to Table 2 below, and the solid content was adjusted to a range of 30 to 60% using ethyl acetate, thereby obtaining a pressure-sensitive adhesive composition.
[0098] The obtained adhesive composition was used to prepare an adhesive sheet according to the procedure described below, and then evaluations were carried out using this adhesive sheet. The evaluation methods and criteria for each item are as follows, and the results are also shown in Table 2 below.
[0099] <Preparation of adhesive sheet> The adhesive composition was applied to a 38 μm thick heavy release silicone separator (manufactured by Mitsui Chemicals Tohcello, Inc., "SPPET03 38BU") using a comma coater so that the dried thickness would be 50 μm, and then dried at 100°C for 3 minutes to form an adhesive layer. A 38 μm thick light release silicone separator (manufactured by Mitsui Chemicals Tohcello, Inc., "SPPET01 38BU") was attached to the surface of the adhesive layer, and then aged at 40°C for 3 days to produce an adhesive sheet (a laminate of light release silicone separator / adhesive layer / heavy release silicone separator).
[0100] [Adhesive strength before heat curing] The light release silicone separator was peeled off from the adhesive sheet prepared above, and the adhesive layer side was bonded to a polyimide film ("Kapton 200H" manufactured by Toray DuPont Co., Ltd.) at room temperature to obtain an adhesive sheet with a film substrate. The heavy release silicone separator was peeled off from the obtained adhesive sheet with a film substrate, and the adhesive layer side was bonded to a SUS304-BA plate at room temperature using a 1 kg roller twice. After 30 minutes, the adhesive strength (N / 25 mm) of the adhesive sheet with a film substrate was measured using an AUTO Graph AG-X Plus (manufactured by Shimadzu Corporation) at a peel speed of 300 mm / min and a peel angle of 180°.
[0101] [Initial adhesive strength after heat curing] The light-release silicone separator was peeled off from the adhesive sheet prepared above, and the adhesive layer side was laminated to a polyimide film ("Kapton 200H" manufactured by Toray DuPont Co., Ltd.) at room temperature to obtain an adhesive sheet with a film substrate. The resulting adhesive sheet with a film substrate was cut into 25 mm widths, the heavy-release silicone separator was peeled off, and the adhesive layer side was laminated to a SUS304-BA plate at room temperature using a 1 kg roller twice, followed by heat curing at 160°C for 1 hour. The temperature was then adjusted to 23°C and 50% RH, and the sheet was peeled off using an AUTO Graph AG-X Plus (manufactured by Shimadzu Corporation) at a peel speed of 300 mm / min and a peel angle of 180°. The initial adhesive strength (N / 25 mm) after heat curing was measured and evaluated according to the following criteria.
[0102] (Evaluation criteria for initial adhesive strength after heat curing) ◎ ·· 30N / 25mm or more ○ 20N / 25mm or more, less than 30N / 25mm × Less than 20N / 25mm
[0103] [Adhesion strength after wet heat test] A test piece (SUS304-BA / adhesive layer / polyimide film) obtained in the same manner as for the initial adhesive strength after heat curing was left to stand for 500 hours in an environment of 85°C x 85% RH, and then the adhesive strength (N / 25 mm) after the wet heat test was measured using the same test method as for the initial adhesive strength. Furthermore, the adhesive strength retention rate was calculated using the following formula and evaluated according to the following criteria.
[0104] (Adhesion strength evaluation criteria after wet heat test) ◎ ·· 30N / 25mm or more ○ 20N / 25mm or more, less than 30N / 25mm × Less than 20N / 25mm
[0105] (Retention rate evaluation criteria) Adhesion retention rate (%) = Adhesion after heat and humidity test / Initial adhesion x 100 ◎ 80% or more 〇 65% or more, less than 80% △ 50% or more, less than 65% × Less than 50%
[0106] [Room temperature transferability] The light release silicone separator was peeled off from the adhesive sheet prepared above, and the adhesive layer side was attached to a polyimide film ("Kapton 200H" manufactured by Toray DuPont Co., Ltd.) at room temperature to obtain an adhesive sheet with a film substrate. When the heavy release silicone separator was peeled off from the obtained adhesive sheet with a film substrate, it was visually confirmed whether the adhesive layer had been transferred to the polyimide film, and evaluated according to the following criteria. (Evaluation criteria) ○ Transcribed × Not transferred
[0107] [Table 1]
[0108] [Table 2]
[0109]
[0062] From the above results, in Examples 1 to 4, which used the pressure-sensitive adhesive composition containing the acrylic resin (A), the epoxy compound (B) and the silane coupling agent (C) specific to the present invention, the decrease in adhesive strength before and after the moist heat test was small, and pressure-sensitive adhesives excellent in durability were obtained. In contrast, Comparative Examples 1 and 2, which contained the epoxy compound (B) but the Tg of the acrylic resin (A) was outside the specific range of the present invention and which did not contain the silane coupling agent (C), were poor in adhesive strength and moist heat resistance after curing. Comparative Examples 3 and 4, which contained the acrylic resin (A) and epoxy compound (B) specific to the present invention but did not contain the silane coupling agent (C), were poor in moist heat resistance. Comparative Examples 5 and 6, which contained the acrylic resin (A) and epoxy compound (B) specific to the present invention but did not contain the mercapto silane coupling agent (C), were poor in adhesive strength retention. These results demonstrate that a pressure-sensitive adhesive with excellent moisture and heat resistance can be obtained by using a specific amount of a liquid epoxy compound in an acrylic resin having a specific glass transition temperature (Tg), and further using a mercapto silane coupling agent. [Industrial Applicability]
[0110] The pressure-sensitive adhesive composition of the present invention has tack and moderate adhesive strength before curing, and can form a pressure-sensitive adhesive having high adhesive strength and excellent moist heat resistance after curing. Therefore, the pressure-sensitive adhesive composition of the present invention can be suitably used for various pressure-sensitive adhesive applications, such as for building materials, in-vehicle parts, electronic parts, semiconductor manufacturing processes, component sealing, aircraft parts, and sporting goods, and is particularly useful for bonding FPCs and reinforcing plates.
Claims
1. A pressure-sensitive adhesive composition comprising an acrylic resin (A), an epoxy compound (B) (excluding (A)) that is liquid at 25°C, a silane coupling agent (C), a curing agent for an epoxy compound (D), and a crosslinking agent for an acrylic resin (E), The glass transition temperature of the acrylic resin (A) is −45 to 60° C., The content of the epoxy compound (B) is 5 to 100 parts by weight based on 100 parts by weight of the acrylic resin (A), The silane coupling agent (C) is a silane coupling agent (C1) having a mercapto group, A pressure-sensitive adhesive composition, characterized in that the crosslinking agent for acrylic resins (E) is an isocyanate crosslinking agent.
2. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the acrylic resin (A) has a weight average molecular weight of 100,000 or more.
3. 3. The pressure-sensitive adhesive composition according to claim 1, wherein the epoxy compound (B) contains an epoxy compound having at least two epoxy groups in one molecule.
4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, characterized in that a content of the silane coupling agent (C) is 0.01 to 3 parts by weight based on 100 parts by weight of the acrylic resin (A).
5. The pressure-sensitive adhesive composition according to any one of claims 1 to 4, wherein the curing agent for epoxy compounds (D) is a powder curing agent.
6. The adhesive composition according to any one of claims 1 to 5, characterized in that the crosslinking agent (E) for acrylic resins contains at least one selected from an adduct of an isocyanate compound and a polyol compound, a biuret of an isocyanate compound, and an isocyanurate.
7. A pressure-sensitive adhesive obtained by crosslinking the pressure-sensitive adhesive composition according to any one of claims 1 to 6.
8. The pressure-sensitive adhesive according to claim 7, which is cured by heating at 100 to 250°C.
9. An adhesive sheet comprising an adhesive layer comprising the adhesive according to claim 7 or 8.
10. A laminate comprising an adhesive layer comprising the adhesive according to claim 7 or 8 and another member laminated thereon.
Citation Information
Patent Citations
Thermosetting dielectric resin composition and thermosetting dielectric resin film
JP2006213797A
Adhesive composition, adhesive sheet and method for manufacturing semiconductor device
JP2009161588A
Pressure-sensitive adhesive composition, pressure-sensitive adhesive, pressure-sensitive adhesive for optical member, optical member with pressure-sensitive adhesive layer, image display device
JP2012077299A
Pressure-sensitive adhesive composition and pressure-sensitive adhesive film and laminate using the same
JP2012171991A
Semiconductor device and semiconductor device manufacturing method
JP2014175459A